The formins Cdc12 and For3 cooperate during contractile ring assembly in cytokinesis - Coffman, Valerie C. (The Rockefeller University Press, 2013)
Both de novo–assembled actin filaments at the division site and existing filaments recruited by directional cortical transport contribute to contractile ring formation during cytokinesis. However, it is unknown which source is more important. Here, we show that fission yeast formin For3 is responsible for node condensation into clumps in the absence of formin Cdc12. For3 localization at the division site depended on the F-BAR protein Cdc15, and for3 deletion was synthetic lethal with mutations that cause defects in contractile ring formation. For3 became essential in cells expressing N-terminal truncations of Cdc12, which were more active in actin assembly but depended on actin filaments for localization to the division site. In tetrad fluorescence microscopy, double mutants of for3 deletion and cdc12 truncations were severely defective in contractile ring assembly and constriction, although cortical transport of actin filaments was normal. Together, these data indicate that different formins cooperate in cytokinesis and that de novo actin assembly at the division site is predominant for contractile ring formation.